242 FALLS-RISK INCREASING DRUGS AND FRAILTY IN OLDER ADULTS EXPERIENCING FALLS: A PROSPECTIVE OBSERVATIONAL STUDY. (25th October 2022) - Randles, M; Gannon, E; Gallagher, P; O'Mahony, D
Abstract: Background: Frailty characteristics such as compromised response to stressors and accumulation of deficits in physiological systems may leave frailer older adults at higher risk of falls, a leading cause of injury and injury-related mortality. One of the more prominent extrinsic risk factors for falls in older adults is the use of Falls-Risk Increasing Drugs (FRIDS). This study aims to examine the relationship between measured frailty and FRIDS in older people who have experienced a fall in the previous 12 months. Methods: A prospective observational study was undertaken. Inclusion criteria were age ≥ 65 years and a history of falling in the preceding 12 months. Exclusion criteria were age <65 years of age, inability to provide informed consent or participation declined. Medical chart and drugs Kardex review was carried out, followed by a short interview with the patient using a standardised data collection proforma. Frailty was measured using the Clinical Frailty Scale (CFS) and the point-prevalence of FRIDS was established using the STOPPFall screening tool. Results: Results are presented for the first 100 participants: The mean (±standard deviation [SD]) age of study participants was 82.1 (±6.2), 63% were female. The prevalence of frailty measured using the CFS was 60% (CFS ≥5). The median number of falls in the previous 12 months was 3 (IQR 3). 82% of people who had fallen in the previous 12 months had ≥1 STOPPFall FRID. The difference between number of FRIDs in Frail vs Non-Frail people was not statistically significant. Conclusion: Prescription of FRIDS was detected in over 4 out 5 older fallers. Structured medication review using the STOPPFall screening tool for older adults at risk of falls is one useful and easy way of detecting FRIDS with a view to deprescription. Measured frailty does not appear to increase the prevalence of FRIDS in older fallers.